1997
DOI: 10.1095/biolreprod56.5.1158
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Messenger Ribonucleic Acid Encoding Luteinizing Hormone Receptor, Cytochrome P450-Side Chain Cleavage, and Aromatase are Associated with Recruitment and Selection of Bovine Ovarian Follicles1

Abstract: The objective of this study was to investigate changes in expression of mRNAs encoding FSH receptor (FSHr), LH receptor (LHr), cytochrome P450 side-chain cleavage (P450(scc)), cytochrome P450 17alpha-hydroxylase (P450(c17)), and cytochrome P450 aromatase (P450(arom)) during recruitment and selection of bovine ovarian follicles. Dairy heifers (4-5 per group) were ovariectomized at 12, 24, 36, 48, 60, 72, 84, or 96 h after initiation of the first follicular wave following estrus as determined by ultrasonography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
138
2
12

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(174 citation statements)
references
References 22 publications
19
138
2
12
Order By: Relevance
“…Bao et al (1997) reported that FSH receptors are present on granulosa cells in some primary follicles in cows; therefore, primary follicles may be able of respond to a low concentration of FSH. The appearance of primary follicles at day 91 was not associated with an increase in oestradiol (in the ovary or the serum content).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bao et al (1997) reported that FSH receptors are present on granulosa cells in some primary follicles in cows; therefore, primary follicles may be able of respond to a low concentration of FSH. The appearance of primary follicles at day 91 was not associated with an increase in oestradiol (in the ovary or the serum content).…”
Section: Discussionmentioning
confidence: 99%
“…The appearance of secondary follicles at day 120 was associated with an increase in serum FSH. Bao et al (1997) reported the presence of FSH receptors on the granulosa cells in secondary and antral follicles. In the present study, the increase in the concentration of FSH at day 120 coincided with the development of primary follicles to secondary follicles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Follicle selection occurs in the face of declining FSH concentrations and is the process by which the growing cohort of follicles is reduced to the ovulatory quota for the species (in cattle it is generally one; Sunderland et al, 1994). The selected follicle survives in an environment of reduced FSH owing to the development of LH receptors in the granulosa cells (Xu et al, 1995;Bao et al 1997) and increased intrafollicular bioavailable IGF-I (Austin et al, 2001;Canty et al, 2006). The increased bioavailable IGF-I is achieved by reduced IGF-I-binding proteins (IGFBP) because of increased IGFBP protease activity.…”
Section: Introductionmentioning
confidence: 99%
“…In heifers, receptors for LH appeared in the granulosa cells of the future dominant follicle about 8 h before the beginning of deviation. In addition, LH-receptor mRNA expression in the granulosa cell layer was limited to follicles that also expressed mRNAs for P450scc and P450arom in the granulosa cells (BAO et al, 1997). The LH stimulates the production of estradiol and insulin-like growth factor-1.…”
Section: Recruitmentmentioning
confidence: 99%